Admiralty jurisdiction in the magistrate's court? - Young, Warren (Centre for Law and Society, 2026)
As children we are introduced to the story of the 'Emperor and his clothes' where the Emperor is duped by some scoundrels, much assisted by his vanity and pride, into believing that they have created for him a suit of the finest and most magnificent cloth. It takes a small innocent child to point out during the procession attended by the Emperor that in fact he is not wearing a suit of finely tailored clothes but nothing at all. The question arises is to whether a Magistrate's Court which claims admiralty jurisdiction is in the same position as that of the Emperor in the story. Does a Magistrate's Court have jurisdiction to hear maritime claims by consent or otherwise or is it a case of a Magistrate's Court attempting to exercise or clothe itself with jurisdiction of this nature merely duped into believing that it has jurisdiction when in fact more exists. In other words, it is jurisdictionally naked.